Permissive Parenting Effect toward Emotional Development of Early Childhood - Nur Hazizah (Universitas Negeri Padang, 2019)
Permissive parenting patterns that can affect emotional development in children is a pattern of care that gives freedom to children without the rules applied and without the responsibilities required by parents to children. The permissive nurturing pattern can have a negative impact on the child's emotional development such as the child often expresses with anger and his emotions can turn into a child who is dissident and difficult to invoke. Children with parenting patterns will tend to be difficult to get along with, do not recognize or cannot control their own emotions, cannot accept defeat, lack of responsibility from within the child. The role of active parents is very much needed and control and the way of care together are expected to reduce the impact of permissive care.